The potential of Sijunzi decoction in the fight against gastrointestinal disorders: a review - Yang, Liangjun; Fang, Zheng; Zhu, Jiajie; Li, Xiaofang; Yang, Bo; Liu, Haiyan; Lou, Feiyan (Frontiers in Pharmacology, 2025)
Sijunzi Decoction (SJZD) is a traditional Chinese medicine formula widely used in the treatment of gastrointestinal disorders. Clinical studies have substantiated the efficacy of SJZD in managing conditions such as functional dyspepsia, chronic gastritis, gastric cancer, irritable bowel syndrome, colorectal cancer, and ulcerative colitis. Despite its proven effectiveness, the precise mechanisms by which SJZD operates remain incompletely understood. In this study, we undertake a systematic review of both the clinical applications and the mechanistic underpinnings of SJZD in the context of gastrointestinal disease treatment. Research indicates that SJZD functions through a spectrum of mechanisms including the regulation of intestinal flora, alleviation of inflammation, modulation of immune responses, and facilitation of mucosal repair in the treatment of gastrointestinal ailments. This comprehensive analysis aims to provide a clearer understanding of how SJZD benefits patients with gastrointestinal disorders.